Overcoming sheaths overlapping in a small diameter metallic tube with one end closed and using a high density plasma from a high power pulsed hollow cathode discharge - M. Ueda; C. Silva; G. B. de Souza; S. F. M. Mariano; L. Pichon (AIP Advances, 2018)
High voltage sheaths are formed when plasmas are produced by application of high negative voltage pulses to conductive supports or components, as in Plasma Immersion Ion Implantation (PIII) treatments of materials surfaces. For parts with concave shape, as inside metal tubes, these sheaths behave quite differently according to the tube configuration and size, as well as, PIII treatment pressure of operation and pulsing parameters. In this work, an SS304 tube of 1.1 cm internal diameter and 20 cm length was pulsed typically at -0.5 to -2.6 kV, 20 μs pulse length, 500 Hz repetition rate, nitrogen pressure of 5x10-2 mbar and with one side closed configuration. Different currents (between 10 and 30 A) were used to produce plasmas with sheaths that overlapped or not, depending on the currents used. To study these sheath behaviors, a simple plasma diagnostic technique based on a bi-dimensional mapping of the deposition of sputtered materials and by etching via the plasma on a Si wafer target surface, both coming out from the tube, was used. This mapping showed clearly the border line situation between overlapping and non-overlapping sheaths in that small tube which allowed to estimate the plasma density to be around 1011 cm-3 at such a sheath condition, as previously anticipated by Sheridan. Above that border condition, nitrogen PIII was successfully obtained in such a small tube of SS304, producing TiN and Ti2N in samples of Ti6Al4V placed inside the tube, when temperatures higher than 800°C were reached there. Below the border, no significant uptake of nitrogen was possible. Using this type of experimental set-up, it is now possible to explore different hollow cathode behaviors, efficient or high temperature (above 800°C) PIII conditions and also new utilizations of the plasma ejected from the tube.